Geodata in labor market research: trends, potentials and perspectives - Kerstin Ostermann; Johann Eppelsheimer; Nina Gläser; Peter Haller; Martina Oertel (Journal for Labour Market Research, 2022)
This article shows the potentials of georeferenced data for labor market research. We review developments in the literature and highlight areas that can benefit from exploiting georeferenced data. Moreover, we share our experiences in geocoding administrative employment data including wage and socioeconomic information of almost the entire German workforce between 2000 and 2017. To make the data easily accessible for research, we create 1-square-kilometer grid cells aggregating a rich set of labor market characteristics and sociodemographics of unprecedented spatial precision. These unique data provide detailed insights into inner-city distributions for all German cities with more than 100,000 inhabitants. Accordingly, we provide an extensive series of maps in the Additional file 1 and describe Berlin and Munich in greater detail. The small-scale maps reveal substantial differences in various labor market aspects within and across cities.
Keywords: J12; J31; O18; R12; 330; Georeferenced data; Labor economics; Microdata; Neighborhood effects; Regional science; Register-based data; Segregation; Spatial economics; Urban economics